ALTERNATIVE ECONOMIC INNNOVATION OF HEMP RESEARCH IN THALIND - Karnasuta, Sujinna (Nimitmai Review Journal, 2021)
Research of hemp in Thailand should be research and development of hemp to benefit the wider community’s economic promotion through community enterprises. Community enterprises located in various locations throughout the country, which have different environments for growing hemp, which in this research, it suggests that they have the effects on the growth, types, and quantity of medical substances in hemp grown from different environments. However, traditional medicine, health products, and biomass products containing important substances obtained from the cultivation of hemp grown in various areas should be researched and developed creatively combining with local wisdom according to the way of life of each region throughout the country. And testing the use of various products should be conducted and then promoting to the market both local and abroad. In the case of utilization for the energy storage industry, the hemp can use the hemp carbon of cellulosic fibers produce as supercapacitors with hemp-based carbon electrodes, some research on hemp-based carbon nanomaterials outperform standard supercapacitors.